If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(1 + 4a) = -114 (1 * 6 + 4a * 6) = -114 (6 + 24a) = -114 Solving 6 + 24a = -114 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 24a = -114 + -6 Combine like terms: 6 + -6 = 0 0 + 24a = -114 + -6 24a = -114 + -6 Combine like terms: -114 + -6 = -120 24a = -120 Divide each side by '24'. a = -5 Simplifying a = -5
| 3(9y+3)-9=2y+21 | | 39+0.75x=x | | (4z+2)+(5z-3)= | | T*4-3=12 | | 5x^2+10x+46=0 | | 14=-0.5x^2+46 | | 3(4x-1)=9x+6 | | 18x-6=20x-12 | | A*5+6=10 | | -30de+12=18d | | 5t+6-2r=7r-10 | | y+9x^3y=0 | | 4x+1=4x-2 | | 3x-5x+3=x-7+10 | | -5(x+2)+3x=-5(x-3)+3x | | 70x^3+112x-1=0 | | 108=-6(x-8)-4x | | 7n=50+24 | | Y-3=-(x-5) | | (5x+y)+(2x+6y)= | | 2(x+9)=26 | | 3*8x=1.5e^2x | | x^4+0.5x^3-6x^2+5=0 | | g-(-7)=13 | | 33=6a+2 | | 20p-(7+2p)= | | z^2+(4+2i)z+(2-3i)=0 | | 39-15y=-31-5y | | 21y^14-7y^4=0 | | 2y-4x=-3-2x+y | | 8x-5=63 | | (3.2+1)-(0.6*7)= |